On Japanese Causative: Review of Shibatani’s Notion of Causative - Shimada, Misaki (Kansas Working Papers in Linguistics, 1990)
In this article, characteristics of Japanese causative constructions are reviewed and discussed based on an article by Masayoshi Shibatani (1976), who has worked extensively in Japanese causative. First, the nature and definitions of the causative are discussed. Then, the types of Japanese causative are presented; finally, a categorization of verbs according to their causativity is suggested. The article concludes by underscoring the value of the notion of causativity and a categorization of verbs.